:SEO & SEMالتسويق عبر محركات البحث أهميتها وفوائدها وطريقة عملها واستراتيجياتها ومدى موافقتها مع الشريعة الإسلامية: THE MARKETING THROUGH SEARCH ENGINES SEO&SEM: IMPORTANCE, BENEFITS, METHOD OF WORK AND STRATEGIES - Al-Rawas, Imad Ahmed Salem Mubarak; Abdul Ghani Azmi, Ilhaamie; Khan, Issa (Online Journal of Islamic Management and Finance (OJIMF), 2023)
Search engine marketing is one of the latest means of e-marketing in the modern era, as it is known by the term (SEO) Search Engine Optimization, one of the completely new ways that marketers use through the use of modern digital tools in order to reach customers, and the main goal of it is to facilitate the link between marketing companies and users When anyone searches through search engines, the link, video, or marketing images appear to them at the top of the search results, which helps them to decide to enter and possibly buy, and therefore the better your pages appear in the search results, the more likely it is to attract attention and attract potential and existing customers to your business. As reports indicate that in 2019, more than $55 billion was spent on search engine marketing, and studies and projections indicate that spending could exceed $86 billion by 2023, which is a huge number and a very strong indicator of the importance of e-marketing for small businesses. The current study follows the descriptive approach by explaining and describing methods, programs, and most important marketing strategies through search engines, where the importance of the research lies in presenting scientific material that highlights the importance of modern marketing methods to enhance the performance of institutions, develop their work, and explain their legal ruling. One of the most important theoretical results of the study is that search engine optimization (SEO) has significant positive results by influencing the number of user visits to small and medium-sized companies' websites, increasing the average duration of user visits, as well as the company's overall sales and revenues generated.